Development of an Arabic text-to-speech system - Zeki, Mustafa; Khalifa, Othman Omran; Naji, A. W. (2010)
Research on Text-to-speech technology has received the interest of professional researchers in many languages which is a consequence of wide range of applications where Text-To-Speech is implemented. However, Arabic language, spoken by millions of people as an official language in 24 different countries, gained less attention compared with other languages despite the fact that it has a religious value for more than 1.6 billion Muslim worldwide. These facts exhibit the need for a high quality, smallsize, and completely free Arabic TTS with the ability of future improvements. The vowelized written text of Arabic language carries the pronunciation rules with limited exceptions, so rulebased system with an exception dictionary for words that fail with those letter-to-phoneme rules may be a much more reasonable approach. This paper is a development of a rulebased text-to-speech Hybrid synthesis system which is a combination formant and concatenation techniques with acceptable naturalness. The simulation results of the system shows good quality in handling word, phrase, and sentence level compared to other available Arabic TTS systems. The accuracy of the overall system is 96%. Further improvements need to be done for stressed syllable position and intonation.